2013
DOI: 10.1177/0018726713482150
|View full text |Cite
|
Sign up to set email alerts
|

When do leaders grant voice? How leaders’ perceptions of followers’ control and belongingness needs affect the enactment of fair procedures

Abstract: Theories that explain employees' positive emotional, cognitive and behavioral responses to fair procedures rely on control and relational processes. In the present study, we build on these models but reverse this perspective to examine when leaders provide voice opportunities in their interactions with employees. We argued that leaders may take care of employees' perceived individual control needs (which influence their own outcomes) by granting them with voice. However, this will be the case particularly when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…As senior managers usually have limited direct interactions with those organization members, the fairness of decision-making procedures becomes one of the few means available to lower-level organization members to evaluate the trustworthiness of senior management. Research has shown that supervisors use information about the needs of their subordinates in shaping the enactment of fair procedures, for instance by giving more voice to those with strong control and belongingness needs (Hoogervorst, De Cremer, & van Dijke, 2013). Given that senior managers will often lack information about the needs of lower-level organization members, the design and enactment of fairly perceived decision-making procedures will likely take time to get acquainted with the concerns present in the organization.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…As senior managers usually have limited direct interactions with those organization members, the fairness of decision-making procedures becomes one of the few means available to lower-level organization members to evaluate the trustworthiness of senior management. Research has shown that supervisors use information about the needs of their subordinates in shaping the enactment of fair procedures, for instance by giving more voice to those with strong control and belongingness needs (Hoogervorst, De Cremer, & van Dijke, 2013). Given that senior managers will often lack information about the needs of lower-level organization members, the design and enactment of fairly perceived decision-making procedures will likely take time to get acquainted with the concerns present in the organization.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…They would either be a leader or a subordinate in the organization, ostensibly based on their responses to items that measured leadership skills. This was to ensure that participants believed that their role in the organization was appointed in a legitimate manner (see Galinsky et al, 2003;Hoogervorst, De Cremer, & Van Dijke, 2013). In reality, we assigned participants randomly to the high or low forgiver power condition.…”
Section: Methodsmentioning
confidence: 99%
“…Empirical studies on justice enactment have used self-assessments of managers, other-assessments through subordinates' ratings of justice perceptions, or measured adherence to rules of justice in a more objective fashion in experimental designs (e.g. Brebels et al, 2011;Hoogervorst et al, 2013;Zapata et al, 2013). In general, research has found substantial correlations between supervisors' self-reported justice enactment and employees' justice perceptions (Huang et al, 2017;Zapata et al, 2013), although some studies have also found manager reports of enacted justice to be unrelated to their subordinates' perceptions of justice (Malmrud et al, 2020).…”
Section: Antecedents Of Self-reported Justice Enactmentmentioning
confidence: 99%
“…In order not to overestimate the importance of AMO predictors for justice enactment, we controlled for individual attributes (demographics and personality), which in previous research have been found to be associated with managerial attitudes and behaviors (e.g. Hoogervorst et al, 2013;Mayer et al, 2007). Demographic characteristics were obtained from company registers and measured participants' age (in years), gender (0 ¼ man, 1 ¼ woman), and number of subordinates.…”
Section: Control Variablesmentioning
confidence: 99%